Gilbert’s Syndrome and the Gut Microbiota – Insights From the Case-Control BILIHEALTH Study - Zöhrer, Patrick A.; Hana, Claudia A.; Seyed Khoei, Nazlisadat; Mölzer, Christine; Hörmann-Wallner, Marlies; Tosevska, Anela; Doberer, Daniel; Marculescu, Rodrig; Bulmer, Andrew C.; Herbold, Craig W.; Berry, David; Wagner, Karl-Heinz (Frontiers in Cellular and Infection Microbiology, 2021)
The heme catabolite bilirubin has anti-inflammatory, anti-oxidative and anti-mutagenic effects and its relation to colorectal cancer (CRC) risk is currently under evaluation. Although the main metabolic steps of bilirubin metabolism, including the formation of stercobilin and urobilin, take place in the human gastrointestinal tract, potential interactions with the human gut microbiota are unexplored. This study investigated, whether gut microbiota composition is altered in Gilbert’s Syndrome (GS), a mild form of chronically elevated serum unconjugated bilirubin (UCB) compared to matched controls. Potential differences in the incidence of CRC-associated bacterial species in GS were also assessed. To this end, a secondary investigation of the BILIHEALTH study was performed, assessing 45 adults with elevated UCB levels (GS) against 45 age- and sex-matched controls (C). Fecal microbiota analysis was performed using 16S rRNA gene sequencing. No association between mildly increased UCB and the composition of the gut microbiota in this healthy cohort was found. The alpha and beta diversity did not differ between C and GS and both groups showed a typical representation of the known dominant phyla. Furthermore, no difference in abundance of Firmicutes and Proteobacteria, which have been associated with the mucosa of CRC patients were observed between the groups. A sequence related to the Christensenella minuta strain YIT 12065 was identified with a weak association value of 0.521 as an indicator species in the GS group. This strain has been previously associated with a lower body mass index, which is typical for the GS phenotype. Overall, sex was the only driver for an identifiable difference in the study groups, as demonstrated by a greater bacterial diversity in women. After adjusting for confounding factors and multiple testing, we can conclude that the GS phenotype does not affect the composition of the human gut microbiota in this generally healthy study group.